Living well with mental illness: Findings from India. Issue 8 (17th November 2021) - S, Aswini; Deb, Amrita
ABSTRACT: In India, mental illness is generally perceived as a lifetime adversity with high vulnerability to problems such as social marginalization, health hazards, and economic deprivation. But anecdotal evidence has shown that many individuals struggling with mental illness have led outstanding lives of courage, dignity and have contributed to society in different ways. Yet scientific research has not focused adequately on such cases and instead has largely studied negative outcomes associated with mental illness. The objective of the present study was to explore positive outcomes through the subjective experiences of individuals diagnosed with mental illness. Interviews of participants (n = 48) were analyzed using thematic analysis. The imperative finding was that despite mental illness and cumulative risks, participants were able to bounce back to a functional level and in a few instances even excelled in specific areas they engaged in. The major implication of such strength-based studies is that it highlights positive outcomes that can assist in building a life of wellness thereby challenging the deficit-based approach that is more popularly followed in studying mental illness. These findings establish that the possibility of living well even after being diagnosed with a mental illness is not a fictional likelihood, rather an achievable reality.